Performance Measurement/Management in Closed-Loop Supply Chain - Kashyap, Karthik (2010)
Reverse logistics and supply chain or the more popular term closed-loop supply chain management is a topic which is gaining speed and popularity during recent years especially due to the various laws and directives laid down by the governments in order to protect environment and the society. Apart from these directives, organisations across various industry sectors are realising this as an opportunity to gain competitive advantage in the supply chain over other organisations and a way of gaining value by remanufacturing and reselling returned goods. However it is only off late that companies have started realizing the importance and advantages of closed-loop supply chain management. Moreover, there were very few articles dealing with reverse supply chains over years and only in recent years have the number of articles gone up. Attempts have been made to provide conceptual and quantitative frameworks in order to help the organisations to operate effectively and gain competitive advantage. However, due to the various differences in the forward and reverse supply chains and various challenges involved in the reverse supply chains, it is particularly difficult to provide a complete framework for reverse logistics and supply chain. Also, very few attempts have been made in order to measure performance in reverse and closed loop supply chains. This dissertation attempts to analyse some of the available performance measurement frameworks for both forward and reverse supply chains and propose a possible framework.